2011
DOI: 10.2337/dc11-0958
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Endogenous Secretory Receptor for Advanced Glycation End Products and Other Factors in Type 2 Diabetic Patients With Mild Cognitive Impairment

Abstract: OBJECTIVEDetermine the serum levels of endogenous secretory receptor for advanced glycation end products (esRAGEs) in patients with type 2 diabetes and mild cognitive impairment (MCI) and in control patients with type 2 diabetes but no MCI, and examine the relationship of esRAGE and MCI with other clinical factors.RESEARCH DESIGN AND METHODSA total of 101 patients with type 2 diabetes who were hospitalized in the Department of Endocrinology at Fujian Provincial Hospital between January 2010 and January 2011 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Skrzep-Poloczek et al demonstrated that AS patients had an increased level of total CHOL and LDL and decreased level of HDL [20]. Chen et al showed that AS patients had elevated levels of total CHOL, LDL and TGs [21]. In rats with AS, the ECs were irregular; for example, the number if ECs vanished, and nuclei were irregular with nuclear pore expansion, while heterochromatin gathered at the periphery of the nuclear membrane and physalides increased in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Skrzep-Poloczek et al demonstrated that AS patients had an increased level of total CHOL and LDL and decreased level of HDL [20]. Chen et al showed that AS patients had elevated levels of total CHOL, LDL and TGs [21]. In rats with AS, the ECs were irregular; for example, the number if ECs vanished, and nuclei were irregular with nuclear pore expansion, while heterochromatin gathered at the periphery of the nuclear membrane and physalides increased in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that found associations with plasma AGEs mostly investigated this in individuals with cognitive impairment or dementia (16,47). In addition, in one recent study, SAF was associated with cognitive impairment (score Ͻ Ϫ1.5 SD in any domain from age-, sex-, and education-adjusted norms) (12).…”
Section: Discussionmentioning
confidence: 98%
“…Yaffe et al (15) have shown that the AGE pentosidine, measured in its free form in urine, was associated with a greater 9-year cognitive decline in older people independent of diabetes status. Furthermore, Chen et al (16) showed that higher levels of serum AGEs were cross-sectionally associated with mild cognitive impairment in diabetes patients. No study to date has investigated the relationship between SAF and cognitive performance on multiple cognitive domains.…”
mentioning
confidence: 98%
“…Another interesting finding that was not emphasized enough was that sRAGEs and esRAGEs seem to have no significant association with classical CVD risk factors such as smoking, lipids, blood pressure, or duration of diabetes, and no more than 6 and 10 % of the variance in sRAGE and esRAGE levels, respectively, was explained by BMI, ethnicity, HbA1c, or eGFR, which goes to show their independent role in predicting CHD events. In a cross-sectional study [70] examining a situation of frank cardiovascular damage, lower serum esRAGE levels and higher serum AGE levels were found associated with dyslipidemia and atherosclerosis in patients with type 2 diabetes. The authors attributed the decrease in serum esRAGE to three possible mechanisms: (1) chronic hyperglycemia directly inhibiting the synthesis and secretion of esRAGEs, (2) the accumulated AGEs binding to esRAGEs and leading to their greater clearance, and (3) inflammation interfering with esRAGE synthesis.…”
Section: Ages and The Age-rage Axis: Clinical Implications In Type 2 mentioning
confidence: 99%